Measuring the orientation of a single CdSe/CdS nanocrystal at the end of a near-field tip for the realization of a versatile active SNOM probe. Issue 24 (7th June 2018) - Jazi, R.; Ung, T. P. L.; Maso, P.; Colas Des Francs, G.; Nasilowski, M.; Dubertret, B.; Hermier, J.-P.; Quélin, X.; Buil, S.
Abstract : The orientation a CdSe/CdS nanocrystal attached at the end of a scanning near field optical microscope (SNOM) tip is analyzed by its coupling with a flat gold layer. Abstract : The orientation of a CdSe/CdS nanocrystal attached at the end of a scanning near field optical microscope (SNOM) tip is analyzed by its coupling with a flat gold layer. The Purcell factors for a set of distances to the gold surface are measured after a NC is caught by a SNOM tip. These measurements are compared with the modeling of the emission of a 2D dipole on a gold layer taking into account the layer of polymer serving as a glue for the NC. The 2D dipole is perpendicular to the c -axis of the NC, which is the growth axis. The behavior of the Purcell factor as a function of the distance to the gold layer depends on the angle made by this axis and the surface. The adjustment of the experimental results and the modelization gives the orientation of the NC at the end of the SNOM tip. Different orientations of the c -axis are determined.